Faktor-Faktor Yang Mempengaruhi Penyaluran Kredit Perbankan Pada Bank Umum Yang Terdaftar Di BEI Periode 2018-2022 - Fernia Arianti Exi Cahyawati; Ida Nurhayati (Universitas Sains dan Teknologi Komputer, 2024)
The purpose of this study is to evaluate and study how Non-Performing Loan (NPL), Third Party Funds (TPF), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Operating Costs to Operating Income (BOPO) affect credit distribution. Quantitative research uses secondary data from the financial statements of banking service companies listed on the Indonesia Stock Exchange in 2018–2022. A sample of 235 companies was collected through a purposive sampling method. Data was processed using the SPSS application. Multiple linear regression analysis was used to conduct this analysis. The results of the study showed that the Non-Performing Loan (NPL) Third Party Funds (TPF) variable with credit distribution did not have a significant positive impact. The Capital Adequacy Ratio (CAR) and Operating Costs to Operating Income (BOPO) variables had a significant negative impact on credit distribution, while the Loan To Deposit Ratio (LDR) variable had a significant positive impact.